PERLINDUNGAN HUKUM TERHADAP HAK ASASI ANAK YANG MENJADI KORBAN KEKERASAN - Azkia, Zuraidah; Is, Muhamad Sadi (Universitas Islam Negeri Raden Fatah Palembang, 2018)
Child rights are an integral part of human rights so that the government must develop the obligation to protect, fulfill and respect the rights of children especially the rights of children who are victims of violence, because violence against children especially in Indonesia is increasing recently. Therefore, the form of legal protection against the rights of children who are victims of violence can be given in a repressive form that is done in a systematic way, through a series of programs, stimulation, training, education, prayer guidance, games and can also be provided through legal aid called advocacy and child protection laws. While the concept of legal protection of child rights in the future must do law reform of child protection system in Indonesia with the aim to give justice, certainty and benefit to children in Indonesia in particular so as to protect and guarantee the rights of children who become victims violence. In order for child protection law in Indonesia in the future to be able to really give protection to child rights which become victims of violence, then child protection law must be free from humanity principle based on human rights.